The Hog1p kinase regulates Aft1p transcription factor to control iron accumulation - Martins, TS (2018)
Iron acquisition systems have to be tightly regulated to assure a continuous supply of iron, since it is essential for survival, but simultaneously to prevent iron overload that is toxic to the cells. In budding yeast, the low‑iron sensing transcription factor Aft1p is a master regulator of the iron regulon. Our previous work revealed that bioactive sphingolipids modulate iron homeostasis as yeast cells lacking the sphingomyelinase Isc1p exhibit an upregulation of the iron regulon. In this study, we show that Isc1p impacts on iron accumulation and localization. Notably, Aft1p is activated in isc1Δ cells due to a decrease in its phosphorylation and an increase in its nuclear levels. Consistently, the expression of a phosphomimetic version of Aft1p-S210/S224 that favours its nuclear export abolished iron accumulation in isc1Δ cells. Notably, the Hog1p kinase, homologue of mammalian p38, interacts with and directly phosphorylates Aft1p at residues S210 and S224. However, Hog1p-Aft1p interaction decreases in isc1Δ cells, which likely contributes to Aft1p dephosphorylation and consequently to Aft1p activation and iron overload in isc1Δ cells. These results suggest that alterations in sphingolipid composition in isc1Δ cells may impact on iron homeostasis by disturbing the regulation of Aft1p by Hog1p. To our knowledge, Hog1p is the first kinase reported to directly regulate Aft1p, impacting on iron homeostasis.